The Role of Vitamins, Minerals, and Nutrition in Leprosy Patients: A Review - Wijaya, Edward; Sutiajaya, Nikita Lestari; Rusyati, Luh Made Mas (Indonesian Journal of Global Health Research, 2024)
Leprosy, is a chronic infectious disease caused by Mycobacterium leprae, an airborne intracellular bacillus and is considered a disease of poverty. Leprosy, with its associated physical and social morbidity, results in economic conditions that lead to malnutrition. The purpose of this study was to explore the role of vitamins, minerals, and nutrition in leprosy patients. The method used in this study was to explore articles and theories related to vitamins, minerals, nutrition and leprosy patients. The results of this study are that decreased antioxidant levels can lead to increased oxidative stress and complications of infectious diseases and leprosy. Because these nutrients have regulatory effects on innate and adaptive immune responses, a perfect balance in their concentrations is important to improve the immune response to pathogens.